2021
DOI: 10.1159/000512558
|View full text |Cite
|
Sign up to set email alerts
|

Acute Response of Human Aortic Endothelial Cells to Loss of Pulsatility as Seen during Cardiopulmonary Bypass

Abstract: Cardiopulmonary bypass (CPB) results in short-term (3–5 h) exposure to flow with diminished pulsatility often referred to as “continuous flow”. It is unclear if short-term exposure to continuous flow influences endothelial function, particularly, changes in levels of pro-inflammatory and pro-angiogenic cytokines. In this study, we used the endothelial cell culture model (ECCM) to evaluate if short-term (≤5 h) reduction in pulsatility alters levels of pro-inflammatory/pro-angiogenic cytokine levels. Human aor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…In 2019, Haglund and others from our group also demonstrated that synchronous and asynchronous flow profiles similar to those of popular CF-VAD models could be replicated, with the synchronous flow requiring some alteration of the compliance element, and the asynchronous flow necessitating the addition of a second pulsatile pump [84]. In a recently accepted but not yet published study of ours, physiologic arterial flow parameters of 120/80 mmHg pressure, 6-10% EC strain, 15 dynes/cm 2 average shear stress, and 10-12 mL/min flow rate at 60-80 beats/min was achieved [85]. They also demonstrated CF-VAD-like parameters of 100 mmHg pressure (pulse pressure completely eliminated) and 12 mL/min flow rate within the same system.…”
Section: Examples Of Vascular Tissue Chipsmentioning
confidence: 87%
“…In 2019, Haglund and others from our group also demonstrated that synchronous and asynchronous flow profiles similar to those of popular CF-VAD models could be replicated, with the synchronous flow requiring some alteration of the compliance element, and the asynchronous flow necessitating the addition of a second pulsatile pump [84]. In a recently accepted but not yet published study of ours, physiologic arterial flow parameters of 120/80 mmHg pressure, 6-10% EC strain, 15 dynes/cm 2 average shear stress, and 10-12 mL/min flow rate at 60-80 beats/min was achieved [85]. They also demonstrated CF-VAD-like parameters of 100 mmHg pressure (pulse pressure completely eliminated) and 12 mL/min flow rate within the same system.…”
Section: Examples Of Vascular Tissue Chipsmentioning
confidence: 87%
“…The Windkessel effect of normal elastic arteries, such as the aorta, decreases the pulsatility of the blood pump out of the heart, converts it into a more constant outflow and thereby prevents damage to the microvasculature [ 21 ]. As this effect is compromised in patients with a PWV > 10 m/s, their microvasculature has to cope with a higher pulsatility, which could initiate the local endothelial cells to start producing more Ang-2 [ 43 , 44 ]. Indeed, Ang-2 was experimentally demonstrated to be involved in arterial stiffness [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…24) Using an ex vivo experimental model of CPB, Nguyen et al showed that short-term exposure (≤5 h) to continuous non-pulsatile flow (vs. pulsatile flow) activated pro-inflammatory/pro-angiogenic signaling in cultured human aortic endothelial cells. 25) Understanding endothelial cell recovery after damage induced by extracorporeal circulation is important to understand the effects of hemodynamic stress after bicuspidalization.…”
Section: Discussionmentioning
confidence: 99%